2004
DOI: 10.4315/0362-028x-67.5.1050
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Brain Emboli following Captive Bolt Stunning of Sheep: Capacity for Entry into the Systemic Arterial Circulation

Abstract: The epidemic of bovine spongiform encephalopathy in the United Kingdom and the recognition of a variant of Creutzfeldt-Jakob disease prompted revision of the guidelines for slaughter of cattle and sheep to prevent contamination of the edible parts of the carcass with central nervous system tissue. We previously showed that captive bolt gun stunning, which is routinely used for the slaughter of cattle and sheep, causes entry of fragments of central nervous system tissue into the jugular vein. To determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many times, when using a captive bolt for slaughter, fragments of bone can be found within brain tissue. This can be attributed to the heavy pressure exerted by the captive bolt at the time of stunning (Coore et al 2004). This heavy pressure can send emboli of brain tissue into the lungs and other organs such as liver (Garland et al 1996).…”
Section: Artifacts Due To the Methods Of Slaughtermentioning
confidence: 99%
“…Many times, when using a captive bolt for slaughter, fragments of bone can be found within brain tissue. This can be attributed to the heavy pressure exerted by the captive bolt at the time of stunning (Coore et al 2004). This heavy pressure can send emboli of brain tissue into the lungs and other organs such as liver (Garland et al 1996).…”
Section: Artifacts Due To the Methods Of Slaughtermentioning
confidence: 99%
“…Drops and aerosols will most likely contaminate the hide surrounding the opening of the head but can also fall on other parts of the carcase (Prendergast et al, 2003;EFSA, 2006b). Stunning-related dissemination of CNS tissue via entry into the bloodstream has also been described (Anil et al, 2002;Coore et al, 2004) suggesting that contamination of hide vessels could be possible. Captive bolts that are not regularly cleaned can contaminate other animals (FAO, 2007).…”
Section: Cross-contamination Of Raw Materials During Slaughtermentioning
confidence: 97%
“…The effectiveness of any mechanical stunning device is dependent on the selection of the proper anatomical site and directional aim of the device. Coore et al (2004) in a study found that 4% of the venous blood sample of cattle (95% confidence interval, 1.6% to 9.8%) stunned using a penetrative captive bolt stunner and from 2% (95% confidence interval, 0.6% to 7%) of cattle stunned using a nonpenetrating captive bolt stunner showed brain tissue fragments or raised levels of a maker protein for brain tissue in the blood. Lambooij et al (1999) concluded experimentally that a modified captive bolt stunning method using air pressure had benefits over electrical water bath stunning for broilers.…”
Section: Preslaughter Stunningmentioning
confidence: 99%